Taxonomic notes on the genus Ectopioglossa Perkins, 1912 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with new records of two species and key to species - Dien, Bui Trong; Manh, Nguyen Thanh; Thai, Mai Van; Thuong, Vu Thi; Lien, Nguyen Thi Phuong (Academia Journal of Biology, 2021)
A taxonomic study on the genus Ectopioglossa Perkins from Vietnam is presented. Two species, E. henseni Gusenleitner, 1990 and E. taiwana (Sonan, 1938), are recorded as new to the vespid fauna of Vietnam. A key to the Ectopioglossa species known from Vietnam is also provided based on external morphological characters.